Star kids 6 (Revised Edition) : A series of theme-based English text books for the students of Elementary School - Aquilina Nikke Paramita; Christina Maryeni; Margareta Ratnaningdyah; Yasinta Dyah Pertiwi K; Maria Tuntun; Harnawan; Flora Maharani (Kanisius, 2019)
Buku ini merupakan buku Bahasa Inggris dasar untuk kelas enam SD